Navigation system for minimally invasive esophagectomy: experimental study in a porcine model - Nickel, Felix; Kenngott, Hannes Götz; Neuhaus, Jochen; Sommer, Christof-Matthias; Gehrig, Tobias; Kolb, Armin; Gondan, Matthias; Radeleff, Boris; Schaible, Anja; Meinzer, Hans-Peter; Gutt, Carsten N.; Müller, Beat P. (Surgical endoscopy and other interventional techniques, 2013)
Navigation systems potentially facilitate minimally invasive esophagectomy and improve patient outcome by improving intraoperative orientation, position estimation of instruments, and identification of lymph nodes and resection margins. The authors’ self-developed navigation system is highly accurate in static environments. This study aimed to test the overall accuracy of the navigation system in a realistic operating room scenario and to identify the different sources of error altering accuracy.